2021
DOI: 10.1097/md.0000000000024847
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors, pathogenic bacteria of maternal sepsis in term pregnant women with positive blood culture during hospitalization

Abstract: The objective of this study was to evaluate the risk factors, pathogenic bacteria and drug sensitivity of maternal sepsis, and provide evidence for clinical prevention and treatment. A retrospective investigation of pregnant women with full-term maternal sepsis was performed to analyze the risk factors, pathogenic bacteria, and drug sensitivity of maternal sepsis. Univariate analysis showed that temperature, serum procalcitonin (PCT) and C-reactive protein (CRP) at admission, white bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Only two studies found the incidence of PROM to be smaller in the non-sepsis than the sepsis group.7,24 Eleven studies found a higher incidence of PROM in the sepsis than the non-sepsis group. 17,18,23,26,27,29,31,33,[37][38][39] In the remaining eight studies, the ORs were not statistically significant. [19][20][21][22]25,28,30,35 Since the data were heterogenous (I 2 =86%), a random effects model was used for analysis.…”
Section: Studies Included In Qualitative Synthesismentioning
confidence: 89%
See 1 more Smart Citation
“…Only two studies found the incidence of PROM to be smaller in the non-sepsis than the sepsis group.7,24 Eleven studies found a higher incidence of PROM in the sepsis than the non-sepsis group. 17,18,23,26,27,29,31,33,[37][38][39] In the remaining eight studies, the ORs were not statistically significant. [19][20][21][22]25,28,30,35 Since the data were heterogenous (I 2 =86%), a random effects model was used for analysis.…”
Section: Studies Included In Qualitative Synthesismentioning
confidence: 89%
“…Wen et al 31 also noted that maternal history of PROM was more common in neonates with sepsis because the need for induced labor increases after PROM, leading to an increase in the frequency of vaginal examinations and further disrupting the balance of normal vaginal flora, weakening the immune system, and increasing the opportunity for pathogenic microorganisms to enter the vagina, blood, uterine cavity, and abdominal cavity through wounds in the reproductive tract and leads to sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Within the existing literature, the majority of studies have taken a broad approach, encompassing all causes of sepsis in pregnant women [2][3][4][5], and very few have specifically examined the impact of urinary tract infections (UTIs), particularly febrile infections, on the development of sepsis and its consequences for both mother and child. Similarly, factors associated with the occurrence of sepsis have been studied regardless of the site of primary infection [2,6,7]. Studies examining pyelonephritis, with or without sepsis, commonly referred to as febrile UTIs [8], have predominantly centered on pyelonephritis as a causative factor for sepsis in pregnant women and its associated antibiotic treatment [9][10][11].…”
Section: Introductionmentioning
confidence: 99%